COST FINDING IN THE PRINTING INDUSTRY. - Brierle, Henry (The Accounting Review, 1926)
Abstract The United Typothetae of America is thirty-nine years old. It began its accounting activities in 1909 and in that year our standard cost finding and accounting system was adopted. The principles of this system have been endorsed by each succeeding annual convention and in the main stand now as originally agreed upon. If two or more salesmen are employed, a separate account should be maintained for salaries and another for commissions. These accounts are then to be further analyzed and classified records kept of performance. If salesmen do work other than strictly selling, proper recognition should be given. An analysis of sales to ascertain to what extent this expense is recovered will be helpful. In arriving at the total selling expense, not only should the direct selling expenses be considered, but all other expenses such as stenographer time, telephone, telegrams, stationery and other incidentals. To make a monthly provision for bad debts is to face facts. Membership in a credit association should not be a substitute for this account. It may, of course, materially reduce the monthly allowance. In addition to making this monthly charge, a careful check-up should be made at stated intervals to ascertain if the monthly provision is adequate.